Konvensi-Konvensi dalam Drama dan Teater Rendra - Nur Sahid (Resital: Jurnal Seni Pertunjukan (Journal of Performing Arts), 2012)
Tujuan penelitian ini adalah untuk mengungkapkan kekhasan proses kreatif Rendra dalam penciptaan karya teater dan drama-dramanya. Konvensi karya drama dan teater Rendra menarik untuk dikaji, sebab Rendra adalah tokoh pembaharu teater modern terkemuka, baik itu dalam bidang penulisan drama, penyutradaraan maupun keaktoran. Kehadirannya dalam khazanah teater Indonesia sangat berpengaruh, sehingga melahirkan sejumlah pengikut dalam penciptaan teater.Kata Kunci: Rendra, konvensi teater, penyutradaraan, drama sosialABSTRACTThe Conventions on Rendra’s Theatre and Drama. The research on the convention analysis of Rendra’s theatrical works and dramas is aimed to reveal the special characteristic of Rendra’s creative process especially on the creation of his theatrical works and dramas. The convention of Rendra’s theatrical works and dramas is interesting to be analyzed since he was famed as the pioneer of modern theater on the field of play writing, play directing, and acting as well. His existence has strongly influenced to the theatrical works, therefore, there can be found some of the followers in creating the theater activities born in the field of theater in Indonesia.Keywords: Rendra, the convention of theater, directing, social critisism